Arhythmorhynchus comptus (Acanthocephala: Polymorphidae) from shorebirds in Patagonia, Argentina, with some comments on a species of profilicollis - Capasso, Sofía Carolina (2016)
Adult and immature Arhythmorhynchus comptus (Acanthocephala: Polymorphidae) were found parasitizing the Baird’s Sandpiper, Calidris bairdii, and the White-rumped Sandpiper, Calidris fuscicollis (Aves: Scolopacidae), from several locations in Patagonia, Argentina. This is the first record of A. comptus in the southern part of South America and from C. fuscicollis and C. bairdii, expanding both its geographical and host distribution. Additionally, immature specimens belonging to the genus Profilicollis were found in both bird species.